2020
DOI: 10.1016/j.jmh.2020.100003
|View full text |Cite
|
Sign up to set email alerts
|

Migrant women and sexual and gender-based violence at the Colombia-Venezuela border: A qualitative study

Abstract: Background Sexual and Gender-Based Violence (SGBV) affects women and girls in multiple ways. During migration and within humanitarian settings, migrant women and girls are exposed to different forms of SGBV and to higher vulnerabilities compared with those men encounter. Survivors of this kind of violence face challenges in accessing healthcare for reasons that not only include legal status, language barriers, discrimination, misinformation on the availability of healthcare services, but also the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 10 publications
1
22
1
4
Order By: Relevance
“…This knowledge of the law and the rules of the shelters were used by some women as a strategy to control the violent behavior of their partners. This situation was different than the findings of a study with Venezuelan migrants in Colombia who reported not being fully aware of the local laws regarding sexual violence and IPV [29]. This difference in knowledge may be because the women in our study were living in UN shelters; in addition, in Colombia, most women reported an irregular legal status.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…This knowledge of the law and the rules of the shelters were used by some women as a strategy to control the violent behavior of their partners. This situation was different than the findings of a study with Venezuelan migrants in Colombia who reported not being fully aware of the local laws regarding sexual violence and IPV [29]. This difference in knowledge may be because the women in our study were living in UN shelters; in addition, in Colombia, most women reported an irregular legal status.…”
Section: Discussioncontrasting
confidence: 96%
“…Migrant women feel more isolated in the situation of domestic violence, frequently with language barriers, a lack of knowledge regarding the services that may help them in this situation, and no knowledge of the ways to access these services [29,41]. Additionally, they are uncomfortable with the possibility of misunderstandings with their cultural and religious beliefs [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…iStock/RadekProcyk special needs during pregnancy or when caring for children but be discriminated against or misinformed over the availability of healthcare services. 7 According to the World Health Organization, little attention is paid to the maternal and newborn health of migrant women and their children compared to the conditions available to nonmigrants. 8 The COVID-19 pandemic has disrupted health services all over the globe, so migrants and refugees are often last in the national public health queues.…”
Section: Violent Trajectoriesmentioning
confidence: 99%
“… 5 In Colombia, for example, recent reports from Venezuelan migrants provide evidence of increased gender-based violence, unmet family planning needs, and inadequate access to maternal health-care services. 6 …”
mentioning
confidence: 99%